Kazimiery Iłłakowiczówny dyskurs o utraconej ojczyźnie - Szpunar, Karolina (Tematy i Konteksty, 2017)
Kazimiera Iłłakowiczówna’s literary output is unusually rich. The poet was born in Vilnius and she spent her youth in Polish Livonia (now Latvia) which topography played a crucial role in her literary work. The loss of this “little homeland” contributed to the specific creation of the country of her childhood. Livonia and Lithuania became for the author of The Lithuanian Nightingale the source of both idyll and pain; the peculiar Way of the Cross. In her works the poet mourns and recalls the lost homeland. She also tries to persuade the warring nations to forgive and make peace. She prays for the disappearance of the borders.